Upaya Guru dalam Mengatasi Sifat Pemalu Anak Usia Dini di TK Dharma Wanita Ponorogo - Putri Dewy Maharani; Priagung Priagung (Institut Agama Islam Sunan Giri Ponorogo, 2025)
In the current era of education, the role of teachers in guiding early childhood development is very important, especially in overcoming obstacles related to social-emotional aspects. One of the challenges often encountered is the shy nature of children, which can affect their interaction patterns both in the classroom and in the wider social environment. For this reason, it is important to know what are the factors that cause shyness in early childhood and what are the efforts made by teachers to overcome this condition. The purpose of this study was to determine the perceptions and efforts of teachers in overcoming shyness in early childhood at TK Dharma Wanita Ponorogo. This research is field research with a descriptive qualitative approach, using data collection techniques through interviews, observation, and documentation. The data obtained were then processed using a qualitative analysis method with inductive reasoning.Based on the results of the study, the most dominant factors causing shyness in children include family environment, personal psychological factors, and limited experience in social interaction. Meanwhile, the efforts made by teachers include providing motivation, creating a supportive learning environment, involving children in group activities, and using a personal approach. The results of this study indicate that with consistent and patient teacher efforts, children gradually show positive changes, such as daring to answer greetings, participate in class activities, and interact with peers.